Migraine Headache : An Overview - Hasan, ASM; Mahmood, Iftekhar; Islam, MR; Khan, MSI; Ali, SM; Tushar, AZ (TAJ: Journal of Teachers Association, 2010)
The history of headache can be traced almost to the beginning of the history of humankind. Among the many causes of it, migraine headache is a debilitating disorder affecting millions of people in the United States and worldwide. The diagnosis of migraine can significantly affect quality of life, health care costs and daily productivity. Hundreds of trials and many guidelines have documented various approaches to migraine management, whether via acute treatment or chronic migraine prophylaxis. Acute or abortive migraine management encompasses specific and nonspecific migraine therapeutics including non-opioid and opioid analgesics, triptans and ergotamines. Prophylactic migraine management data span the pharmacological spectrum from antiepileptic and antihypertensive agents to botulinum toxin type A. Special considerations for migraine management also must be applied in various populations including children, pregnant women and the elderly. Although hundreds of clinical trials are available regarding migraine treatment modalities, this review serves as an introduction to current accepted therapeutics for migraine treatment and an overview of pharmacological prophylaxis in the modern management of migraine. TAJ 2010; 23(1): 114-119